Voices of Vlogging - Biel, Joan-Isaac; Gatica-Perez, Daniel (Proceedings of the International AAAI Conference on Web and Social Media, 2010)
Vlogs have rapidly evolved from the ’chat from your bedroom’ format to a highly creative form of expression and communication. However, despite the high popularity of vlogging, automatic analysis of conversational vlogs have not been attempted in the literature. In this paper, we present a novel analysis of conversational vlogs based on the characterization of vloggers’ nonverbal behavior. We investigate the use of four nonverbal cues extracted automatically from the audio channel to measure the behavior of vloggers and explore the relation to their degree of popularity and that of their videos. Our study is validated on over 2200 videos and 150 hours of data, and shows that one nonverbal cue (speaking time) is correlated with levels of popularity with a medium size effect.